Topical Clover Flower Honey Administration Accelerated Wound Healing in Swiss Webster Mice - Hans Kristian; Iwan Budiman; Stella T Hasianna (Journal of Medicine and Health, 2018)
AbstractClover flower honey is a herbal therapy used as an alternative wound treatment. The objective of this study was to determine the effect of Clover flower honey in accelerating incision wound healing, enhancing reepithelization degree, increasing fibroblast density, and collagen. This was a true experimental research, using 25 mice divided into 5 groups (n=5); positive control group (feracrylum 1%), negative control group (aquadest), 100% honey group, 50% honey group, and 25% honey group. Wound healing activity was measured macroscopically with calipers, dan microscopically through pathological anatomy preparations to observe reepithelization degree and collagen density. This study showed wound incision lengths were different significantly between Clover flower honey 100%, 50%, and 25% compared to aquadest (p ≤ 0.05), and feracrylum 1% (p ≤ 0.05). Reepithelization degree, fibroblast and collagen density measurements between Clover flower honey 100%, 50%, and 25% were different significantly compared with aquadest (p ≤ 0.05), and only the 100% honey group was different significantly with feracrylum 1% (p ≤ 0.05). We concluded topical Clover flower honey administration accelerated wound healing, increased reepithelization degree, fibroblast density, and collagen degree.Keywords : wound healing, reepithelization degree, fibroblast density, collagen density, Clover flower honey